Professional competence as the main indicator of the quality of training of future occupational health and safety specialists - Bilyk, R. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to theoretical substantiation of the procedure of developing professional competences of future occupational health and safety specialists. It considers pedagogical conditions of the process of formation of psychological, methodological, subject-related, functional (related to occupational safety) and communicative competences of future occupational health and safety specialists. Special emphasis is put on the necessity to improve the quality of vocational training of specialists in the field of occupational health and safety as well as to ensure its compliance with the requirements of modern high-tech production industries. The article analyses the state of provision of the labour market with certified occupational health and safety specialists. On the basis of statistical data, it is proved that the labour market today experiences a significant lack of these specialists. Scientific approaches adopted by different researchers concerning the composition and structure of professional competencies are considered, the content of these socially important qualities of future occupational health and safety specialists is determined. The key concepts of the research, such as "professional competence", "functional competence", " occupational health and safety competence", and possible ways of their development in the process of training such specialist are analysed. The article considers professional competence of a future occupational health and safety specialist as an integrated professional and personal characteristic, which is a reflection of their professionalism, readiness to perform professional functions and duties, constant drive for selfdevelopment and self-improvement in order to increase their professional level. The article may be useful while training VET teachers in educational institutions of different levels; for heads of occupational safety offices; insurance experts on occupational health and safety; occupational health and safety specialists; operators of technical means of hazard control; specialists on fire safety; experts on industrial safety; specialists on technogenic and environmental safety; experts on working conditions; inspectors on occupational health and safety.